PENGARUH CURRENT RATIO (CR), DEBT TO EQUITY RATIO (DER), RETURN ON EQUITY (ROE), DAN UMUR PERUSAHAAN TERHADAP HARGA SAHAM - Suci Herawati; Dicky Arisudhana (Jurnal Ilmiah Manajemen dan Akuntansi, 2025)
This study aims to examine the effect of Current Ratio, Debt to Equity Ratio. Return On Equity, Company Age on Stock Price. Current Ratio, Debt to Equity Ratio, Return On Equity, Company Age as independent variables. While Stock Price as the dependent variable. This study uses secondary data with a population of 44 companies, namely nickel sub-sector mining companies listed on the Indonesia Stock Exchange in 2021-2024, as many as 13 (thirteen) companies that are research samples with observation years 2021-2024. The sampling technique used is purposive sampling with multiple linear regression analysis methods. The results of this study indicate that simultaneously Current Ratio, Debt to Equity Ratio, Return On Equity, Company Age have an effect on Stock Price. Partially Current Ratio, Return On Equity, Company Age have no effect on Stock Price while Debt to Equity Ratio has an effect on Stock Price.